SISTEM INFORMASI AKUNTANSI PEMBIAYAAN MUDHARABAH PADA BANK MUAMALAT KANTOR CABANG PEMBANTU BONE (BERDASARKAN PRINSIP AKUNTANSI SYARIAH) - Saenal, Saenal; Idrus, Muhammad; Mustadir, Mustadir (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2024)
Research Objectives: To find out how the financing accounting information system worksmudharabahat Bank Muamalat Bone Sub-Branch Office, to find out the obstacles that arise in the financing processmudharabahat Bank Muamalat Bone Sub-Branch Office, to find out what the financing accounting information system ismudharabahat Bank Muamalat Bone Sub-Branch Office, this has been carried out based on sharia accounting principles. This research uses descriptive qualitative research. Descriptive qualitative research is research that attempts to describe a symptom, event or event that is happening now. Research results 1) Show that the process of collecting and storing transaction activity data at Bank Muamalat has been carried out using computers assisted by certain applications that help employees in the process of collecting and storing data, so that if at any time it is needed it will make things easier for employees. 2) Shows that there are still obstacles that occur in the mudharabah financing process, including the customer's lack of understanding about sharia principles, especially mudharabah, the bank's lack of concern for customer limitations which is manifested in the form of preparing the bank's strategy for risk management, and the lack of human resource knowledge about the characteristics of mudharabah financing. . 3) Shows that the mudharabah financing accounting information system at PT. Bank Muamalat Bone Sub-Branch Office has been implemented based on sharia accounting principles, namely the principles of responsibility, justice and truth. These three principles have been applied in the financing process.